Coraline - Gaiman, Neil; McKean, Dave (New York HarperEntertainment, 2008)
Looking for excitement, Coraline ventures through a mysterious door into a world that is similar, yet disturbingly different from her own, where she must challenge a gruesome entity in order to save herself, her parents, and the souls of three others.
Keywords: Supernatural -- Juvenile fiction; Young adult fiction